Anaesthetic and analgesic eects of adding fentanyl to bupivacaine-lignocaine mixtures in supraclavicular brachial plexus block a comparative study with or without fentanyl - Zainab, Farhanaz; Faruq, Mohammad Omar; Talukder, Moumita; Yeasmeen, Sabina; Alam, AKM Shamsul; Haque, AKM Faizul (Bangladesh Medical Journal, 2016)
Brachial plexus block is gaining popularity day by day for upper extremity surgery because it has manifold advantages. Supraclavicular approach offers a high success rate for elbow, forearm, hand surgery. Different mixtures of local anesthetics are intended to provide faster block onset than long-acting agents and to extend the duration typically seen with intermediate or short-acting agents. This prospective, randomized comparative study was conducted to compare the onset time of sensory block, onset time of motor block and time to achieve complete block, duration of analgesia adding fentanyl with bupivacaine-lignocaine mixtures in supraclavicular brachial plexus block. A total of 60 patients fulfilling the inclusion and exclusion criteria were selected for the study & devided into two groups. Group A received lignocaine-bupivacaine mixtures( 1% lignocaine, 0.25% bupivacaine) and was considered control; group Group B received fentanyl (100?g) with the local anaesthetic mixtures( 1% lignocaine, 0.25% bupivacaine). The mean onset of sensory and motor block were significantly early in group B compared with that of group A. The mean time to achieve complete block and duration of analgesia were significantly longer in group B. It was revealed in the study that patients of group B had no pain up to 4 hrs, there was first reporting of pain (VAS >4) around 5 hrs, the worst pain was experienced after 8 hrs, first dose of analgesic was administered according to patients request. The patients of group A had no pain up to 3 hrs. Thereafter pain intensity increased at 4 hrs, around 6 hrs postoperatively the patients experienced the worst pain . This feature reveals a significantly longer duration of analgesia in group B. This study revealed that addition of fentanyl significantly causes early onset of anaesthesia and longer duration of analgesia without any side effects. Bangladesh Med J. 2015 Jan; 44 (1): 26-31